Agent Based Access Point Selection Mechanism - Vijayan, Vinodh P; George, Neema; Kurian, Simy Mary; Sujitha, M (International Journal of Computer Sciences and Engineering, 2025)
The last few years have visible a brilliant boom in the deployment of 802.Eleven Wireless Local Area Networks (WLANs). The proliferation of wi-fi users and the promise of converged voice, information and video technology is predicted to open new numerous possibilities for 802.Eleven based totally WLANs in the networking market.When the WLAN design turned into first advanced in 1990, the model assumes that a WLAN deployment accommodates one stand on my own Access Point (AP).In truth, any such device gives exceptional consumer experience as lengthy as there may be few customers with exceptionally light site visitors load and one AP. Due to fast boom of wireless users and the requirement for continuous insurance, multi-AP WLANs now a days span homes or floors. Some neighboring APs have to be configured on the same channel due to the constrained quantity of channels the 802.11 fashionable supports.In WLANs frequently a station can doubtlessly companion with multiple AP. Therefore, a relevant query is which AP to pick out great from a list of candidate ones. In IEEE 802.Eleven, the consumer certainly buddies to the get entry to factor with the most powerful acquired sign strength.Hence a multiobjective technique(ie.More than one parameters are taken into consideration)and fuzzy primarily based selection making is proposed.Here every node are handled as agent which looking to access first-class AP.Fuzzy based totally decision making ensures effective usage of professional information.